Influence of the economic crisis on the European Union’s climate policy and its consequences for the Polish power industry and land use within Poland - Dunal, Patryk; Płaziak, Monika (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
Climate Regulations imposed by the European Union affect the Polish energy sector unequally, compared to other countries, mainly due to the dominance of coal as main resource in energy production. The effects of the global economic crisis, which started in 2007 in the United States, could change the climate policy in Europe, and thus contribute to changing the direction of Polish power industry development and spatial development of the country. Continuing with the current climate policy in the upcoming years will cause the reduction of the use of coal in the fuel structure of Polish power industry. The role of renewable energy will increase and almost half of this type of energy will be produced by wind power, mainly due to the geographical location of Poland. To ensure the effectiveness of the new systems, proper infrastructure needs to be developed, in particular transmission networks within the country, as wells as connections with neighbouring countries: Germany, Slovakia, Lithuania and Ukraine. Moreover, it is desirable to integrate with the Nordic energy systems. The powers-that-be in coal industry for several years now have attempted to save conventional energy by implementing projects reducing the risk associated with investments in the coal sector and supporting marketing campaigns that promote Polish coal. Nowadays, research and development centres are working on various applications for modern clean power generation technologies, which base on solids that limit greenhouse gas emissions. In the case of easing on the climate policy of the EU as a result of the global economic crisis, expensive investments reducing CO2 emission would be deferred. In such a case, the domination of coal and lignite in Polish energy sector is inevitable, due to its relatively low cost and high energy efficiency. Coal plants would be in good financial shape. Gas power plants would be mainly used as support during periods of peak energy consumption. The production of renewable energy, biomass and biogas would not be enforced. Nuclear power would not be proposed. In the case of strict climate policy, Polish coal sector would be replaced by other energy sources, in particular renewables. To achieve this effect, regulations enhancing the attractiveness of investing in installations using renewable energy sources would be introduced, while the profitability of conventional power plants would be reduced by raising the price of CO2 emission allowances, such as the European Commission’s approval of the plan of black loading, implementation into the Polish legal system a “small triple energy package”, and a “big triple energy package”. Decarbonisation policy would enable the development of nuclear energy and the production of energy from renewable sources. In Polish conditions, a climate policy that is too restrictive may lead to degradation of economy, as an increase in the price of energy would result in an increase of operational costs for most companies. On the other hand, under certain conditions created by the relevant laws and institutions, the allocation of resources in sectors of low carbon technologies could lead to the development of innovative technologies, economic growth, and job creation, for example in the production of equipment for the energy sector, in construction and assembly companies, energetic agriculture, in the acquiring and processing of biomass fuels. Decarbonisation may be beneficial only in the distant future. The upcoming year-long Polish Presidency at the International Climate Convention could be a major opportunity to strengthen the Polish position and a chance to enforce the regulations favourable to the Polish energy industry.